Chinese investment in Africa: How much do we know? - Bräutigam, Deborah; Diao, Xinshen; McMillan, Margaret S.; Silver, Jed (Centre For Economic Policy Research, 2019)
There is a widespread belief that China plays a fundamental role in African economies, but few rigorous empirical studies to back up this view. Many reports describe China’s engagement with Africa as “neo-imperialism” and “authoritarian capitalism”, exploiting natural resources and local labour while undermining democracy. A growing demand for natural resources in China is also credited with boosting growth across the continent, especially in Africa’s resource-rich countries. In this paper, Brautigam, Diao, McMillan and Silver (2016) present a more balanced and data-driven view on what we know about Chinese investment in Africa and what it means for growth. The authors use official Chinese data to examine the patterns of Chinese engagement in Africa for the period 1998 to 2015. Importantly, these data show large gaps between planned and realised investment. They distinguish between these, and focus only on realised investments. The data indicate that China’s influence in Africa is much smaller than is generally believed, though its engagement on the continent is increasing. Chinese investment in Africa, while less extensive than often assumed, has the potential to generate jobs and development on the continent.